Implementation of Sharia Compliance at Sultan Agung Sharia Hospital Semarang - Ilham Mashuri; Sabrina Kamalin; Mahirotin N.; Nidza Novriza (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2024)
The halal industry continues to develop along with the awareness of Muslims to consume and live a lifestyle that is by sharia principles. This research aims to first review and analyse the importance of Shariah compliance in the Sharia hospital industry in Indonesia, second review the regulatory framework for Shariah compliance in Sharia hospitals, third review the implementation of Shariah compliance (SC) in the Sultan Agung Semarang Sharia hospital. This research is empirical juridical research with qualitative descriptive analysis techniques. The results of this study indicate that first, shariah compliance in Sharia hospitals is a must because Shariah compliance is the hallmark of this industry from conventional industries and will maintain the sustainability of this industry because the interests of Muslim consumers are guarded and protected. Secondly, the regulatory framework of Islamic hospitals consists of scattered several regulations, namely Law Number 33 of 2014 concerning Halal Product Guarantee, Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 8 of 1999 concerning Consumer Protection (UUPK), Fatwa DSN MUI Number: 107/DSN-MUI/X/2016 concerning Guidelines for Hospitals Based on Sharia Principles. The regulations scattered in various rules do not specifically regulate Islamic hospitals, so these regulations are not adequate for regulating Islamic hospitals. In terms of SC implementation, there are various obstacles, including in medicines, where halal pharmaceuticals are still limited, as well as the use of Islamic financial institutions in transactions that have not been fully used.